Polymer brush functionalized SiO2 nanoparticle based Nafion nanocomposites: a novel avenue to low-humidity proton conducting membranes1. Issue 31 (21st August 2015) - Farrukh, Aleeza; Ashraf, Fatima; Kaltbeitzel, Anke; Ling, Xiao; Wagner, Manfred; Duran, Hatice; Ghaffar, Abdul; ur Rehman, Habib; Parekh, Sapun H.; Domke, Katrin F.; Yameen, Basit
<x xml:space="preserve">Abstract</x> Polymer brush grafted SiO2 NPs provide Nafion nanocomposite membranes with superior proton conductivities at ambient and moderately high temperatures over the entire range of relative humidity.